Farming Human Pathogens Ecological Resilience and Evolutionary Process - Wallace, Rodrick; Wallace, Deborah; Wallace, Robert G. (Springer New York : Imprint: Springer, 2009)
Farming Human Pathogens: Ecological Resilience and Evolutionary Process introduces a cutting-edge formalism based on the asymptotic limit theorems of information theory to describe how punctuated shifts in mesoscale ecosystems can entrain patterns of gene expression and organismal evolution. The development is applied to several infectious diseases that have evolved in response to the world as humans have made it. Many pathogens emerging from underneath epidemiological control are 'farmed' in the metaphorical sense, as the evolution of drug resistant HIV makes clear, but some, like avian influenza, emerge quite literally as the result of new practices in industrial farming. Effective disease control in the 21st Century must necessarily involve broad economic and social reform for reasons embedded in the basics of pathogen evolution. .